Nutritional levels of digestible methionine + cystine to brown-egg laying hens from 50 to 66 weeks of age - Polese,Clauber (2012)
The objective of this study was to determine the requirement of digestible methionine + cystine of brown-eggs laying hens from 50 to 66 weeks age at the end of the first production cycle. The design was completely randomized, with 150 Brown Shaver hens, which were distributed in five treatments with six replications of five birds each. Birds received a basal diet with 2857 kcal/kg metabolizable energy and 15.97% crude protein, supplemented with 0.132; 0.174, 0.215, 0.256 and 0.298% DL-methionine (98%), in order to provide 0.572, 0.613, 0.653, 0.693 and 0.734% digestible methionine + cystine. The levels of digestible methionine + digestible cystine followed, respectively, the relations of 67, 72, 77, 81 and 86% with lysine fixed at 0.851%. Feed intake, methionine + cystine intake, feed conversion per dozen eggs, egg weigth and mass, percentage of egg components, internal egg quality and weight gain were evaluated. Methionine + cystine levels showed a quadratic effect on feed conversion per dozen eggs and egg weight, a linear effect on feed conversion per kilogram of eggs and percentage of albumen. There was also a positive linear effect on yolk percentage. The methionine + cystine requirement was estimated at 0.572%, corresponding to 682 mg of digestible methionine + cystine/bird/day.